Lecturers’ language problems in writing english papers for international publications - Hartono Hartono; Ruseno Arjanggi; Kurniawan Yudhi Nugroho; Ira Alia Maerani (Intelektual Pustaka Media Utama, 2019)
Indonesian lecturers are now encouraged to publish papers in international journals so that they can better disseminate research findings and innovations globally. However, many of them have the problems with English language mastery. This study was aimed at identifying and analyzing language problems of the Indonesian university lecturers in writing English academic papers for international publications. The subjects of the study were 66 randomly selected lecturers of various disciplines other than English Education and English Literature. The data were collected by questionnaire and English writing tasks on phrases, sentences, and paragraphs which were then analyzed descriptively. The results show that language errors and mistakes in grammar, syntax, vocabulary, spelling and word forms were all found in the subjects’ writings. In writing academic papers for international publications, university lecturers faced language problems as constructing phrases and sentences, choosing and using appropriate vocabulary and terms relevant to their topic of study as well as translating their Indonesian sentences into English.